The South American Physical Activity and Sedentary Behavior Network (SAPASEN) - Werneck, André O. [UNESP] (2019)
The present article describes the South American Physical Activity and Sedentary Behavior Network, which was designed to provide ongoing transnational empirical evidence about physical activity and sedentary behavior in South America. The first goal of this initiative was to form a representative body of researchers and policy makers from all South American countries (Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Guyana, Paraguay, Peru, Suriname, Uruguay and Venezuela) to establish priorities and targets for the short, medium and long term. Examples are given of connecting physical activity and sedentary data from existing surveys in several of the partner countries. The main objective of the South American Physical Activity and Sedentary Behavior Network will be to impact policies on physical activity and sedentary behavior in South America according to the singularities of each country or region. By encouraging an inclusive and collaborative effort, we expect that the South American Physical Activity and Sedentary Behavior Network will support the connection between researchers from South America as well as provide a better comprehension of the epidemiology of physical activity and sedentary behavior regionally.